Scattering of a whispering gallery mode by a cylindrically curved impedance strip - Alinur, Büyükaksoy (Elsevier BV, 1985)
The analysis of edge-diffracted waves generated by the edge of a curved impedance sheet is of great importance for both theoretical and practical applications. This problem is considered here for a cylindrically curved strip illuminated by a whispering gallery mode, and is solved by reducing it to a matrix Hilbert equation. All the results are stated according to the terminology of the geometrical theory of diffraction (GDT). The expression for several transfer (diffraction) coefficients are obtained in explicit forms. Though these expressions were derived for this particular geometry, they can be useful in the analysis of more complicated structures. When the impedance of the curved strip becomes zero, then all the expressions are reduced to known expressions related to the perfectly conducting sheet.
Keywords: Wave scattering in solid mechanics; transfer (diffraction) coefficients; geometrical theory of diffraction; edge-diffracted waves; cylindrically curved strip; matrix Hilbert equation; explicit forms; whispering gallery mode